Integrasi Praktik Komunikasi Digital dan Corporate Branding di Lingkungan Industri Strategis PT PAL Indonesia - Haqqi , Alex Mohammad L. (Dimar Jaya Publishing, 2025)
This study aims to analyze and evaluate the integration of digital communication practices with corporate branding strategies in the strategic industrial environment of PT PAL Indonesia. The research method used is a qualitative approach with case studies, through in-depth interviews, participatory observation, and analysis of company communication documentation. The results of the study show that: Digital communication is a strategic tool for strengthening corporate branding and corporate identity through consistent digital messaging. Stakeholder engagement has increased through digital platforms, and corporate branding supports strategic industrial diplomacy. The use of social media, official websites, and other digital channels has strengthened corporate brand positioning, increased stakeholder engagement, and supported the institution's reputation as a national strategic industry.